2007
DOI: 10.1210/me.2006-0304
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Effects on Breast Cancer Cell Proliferation, Proteases Activation, andin VivoDevelopment of Metastatic Phenotype All Depend on Progesterone Receptor Capacity to Activate Cytoplasmic Signaling Pathways

Abstract: Accumulating evidence indicates that progestins are involved in controlling mammary gland tumorigenesis. Here, we assessed the molecular mechanisms of progestin action in breast cancer models with different phenotypes. We examined C4HD cells, an estrogen (ER) and progesterone (PR) receptor-positive murine breast cancer model in which progestins exert sustained proliferative response, the LM3 murine metastatic mammary tumor cell line, which lacks PR and ER expression, and human PR null T47D-Y breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 65 publications
6
68
1
Order By: Relevance
“…However, these effects are ligand, PGR isoform and context dependent. In general, progestins acting through nuclear PGR inhibit cell migration and invasiveness (Lin et al 2000, 2001, McGowan et al 2004, Carnevale et al 2007. In cells transfected with PGR, progestin treatment increases actin stress fibers and focal contacts, consistent with increased adhesion and decreased migration (Lin et al 2000(Lin et al , 2001.…”
Section: Estrogen Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these effects are ligand, PGR isoform and context dependent. In general, progestins acting through nuclear PGR inhibit cell migration and invasiveness (Lin et al 2000, 2001, McGowan et al 2004, Carnevale et al 2007. In cells transfected with PGR, progestin treatment increases actin stress fibers and focal contacts, consistent with increased adhesion and decreased migration (Lin et al 2000(Lin et al , 2001.…”
Section: Estrogen Receptorsmentioning
confidence: 99%
“…Using a DNA-binding mutant PGR, Carnevale and coworkers (Carnevale et al 2007) reported that PGR activated cytoplasmic signaling cascades that contributed to breast cancer metastasis. Progestin activation of MAPK, PI3K/Akt and GTPase/RhoA modulated the expression of genes such as urokinase plasminogen activator (uPA), uPA receptor (uPAR), matrix metalloproteases (MMPs), β1-integrin and PAI-1 (Carnevale et al 2007, Bellance et al 2013 suggesting a mechanism through which migration is increased by progestins.…”
Section: Estrogen Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These murine cells lacked progesterone receptor (PR) and estrogen receptor (ER) expression [29]. The LM3 cells were kindly provided by Dr. Elisa Bal from Roffo Hospital, Buenos AiresArgentina.…”
Section: Lm3 Cell Culturesmentioning
confidence: 99%